2018
DOI: 10.1016/j.ejca.2018.01.067
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of brain metastases screening and management in non-small cell lung cancer in Europe: Results of the European Organisation for Research and Treatment of Cancer Lung Cancer Group survey

Abstract: BM management is highly variable in Europe: screening is not uniform, prognostic classifications are not often used and MUT+ NSCLC patients generally receive more intensive local treatment. Prospective assessment of BM management in MUT+ NSCLC patients is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 42 publications
1
58
0
Order By: Relevance
“…Recent real world data collected by EORTC Lung Cancer Group showed that NSCLC patients with driver mutations generally received more intensive local treatments . Further, a recent large‐scale retrospective study of EGFR ‐mutant NSCLC patients with BMs reported that survival time was improved by the combination of upfront SRS and EGFR‐TKI compared to that by upfront WBRT and EGFR‐TKI or TKI monotherapy (46 months vs. 30 months vs. 25 months, P < 0.001) .…”
Section: Discussionmentioning
confidence: 99%
“…Recent real world data collected by EORTC Lung Cancer Group showed that NSCLC patients with driver mutations generally received more intensive local treatments . Further, a recent large‐scale retrospective study of EGFR ‐mutant NSCLC patients with BMs reported that survival time was improved by the combination of upfront SRS and EGFR‐TKI compared to that by upfront WBRT and EGFR‐TKI or TKI monotherapy (46 months vs. 30 months vs. 25 months, P < 0.001) .…”
Section: Discussionmentioning
confidence: 99%
“…An important factor which impoverishes patient prognosis is the presence of brain metastases (BM), a relatively frequent metastatic site for lung tumors. Baseline BM are present in 10% of non‐small cell lung cancer (NSCLC) patients, and this number is expected to increase with the standardization of brain imaging in asymptomatic patients, particularly in those with specific molecular alterations, such as EGFR mutations ( EGFR m) or ALK rearrangements ( ALK r), but also in those with elevated CEA . Additionally, the risk of presenting BM increases throughout the course of the disease, and overall 40% of NSCLC patients will eventually present BM, although this proportion increases to 80% in particular subgroups .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Additionally, the risk of presenting BM increases throughout the course of the disease, and overall 40% of NSCLC patients will eventually present BM, although this proportion increases to 80% in particular subgroups. 4 BM usually leads to treatment failure and impaired quality of life despite treatment 4 ; moreover, the prognosis of BM is poor, with a median survival of two months when treated with systemic corticosteroids alone. Whole brain irradiation (WBI) and stereotactic radiosurgery (SRS) have been the mainstay treatment for BM in NSCLC patients irrespective of histology with objective response rates (ORR) of 60%-70% for intracranial lesions and a median survival of eight months.…”
Section: Introductionmentioning
confidence: 99%
“…Surveys of lung cancer clinicians have found that 49% of UK clinicians and 85% of EORTC clinicians would routinely screen brains of neurologically asymptomatic patients . The use of screening differed by stage.…”
mentioning
confidence: 99%
“…Surveys of lung cancer clinicians have found that 49% of UK clinicians and 85% of EORTC clinicians would routinely screen brains of neurologically asymptomatic patients. 2,3 The use of screening differed by stage. In the EORTC study, screening by stage was 39% for Stage I and II, 63% for Stage III and 43% for Stage IV NSCLC patients 3 compared to 34% Stage I, 41% Stage II, 50% Stage III and 40% Stage IV reported by Diaz et al 1 The figures are similar except for a higher proportion of EORTC clinicians stating that they would screen Stage III patients.…”
mentioning
confidence: 99%